IMPLEMENTASI ALGORITMA BLUM BLUM SHUB PADA KUIS SANDI SEMAPHORE BERBASIS AUGMENTED REALITY - Ridwan Alamsyah; Erlan Darmawan; Rio Andriyat; Yulyanto; Suseno, Endra (FKOM UNIKU, 2023)
Semaphore is a way to send and receive news by using a flag, paddle, trunk, bare hands or gloves. The semaphore learning at School at this time still uses the Scout's manual and it is only in the form of 2D images and it is also delivered by the Scout coach. So that students tend to get bored in learning the semaphore movement and lack of understanding and education in the learning process in this modern era. From the existing problems, the semaphore movement learning application and semaphore quiz were built using augmented reality technology based on android to provide interesting and interactive learning. This application was built by adding the Blum-Blum Shub (BBS) algorithm for the randomization process which functions to generate random numbers in a mathematical process with the resulting output is a series of binary numbers. Application created uses Unity 3D, and developed uses the RUP (Rational Unifed Process) method. With this application, it can make easier for students to understand the material in semaphore learning